Pengaruh Kompensasi, Motivasi, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan di Konsultan Pajak Drs. Lim Yung San dan Rekan - Alienda Retnosari P. (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
The aim of this research is to know the influence of compensation, motivation, and office environment toward the employee satisfaction on working. The method of this research is quantitative method. Double regression was used to analyze the data. The population of this research was all employees of Lim Yung San and Partner Tax Consultant. Sampling method is Total Sampling. The result of this research is compensation, motivation, and office environment have positive and significant effect toward the employee satisfaction to the employee of Lim Yung San and Partner Tax Consultant. Based on that result, the Tax Consultant have to concern to maintain the employee performance through the compensation, motivation, and office environment.